2010
DOI: 10.1210/jc.2009-2481
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis-Like Weak Inducer of Apoptosis as a Proinflammatory Cytokine in Human Adipocyte Cells: Up-Regulation in Severe Obesity Is Mediated by Inflammation But Not Hypoxia

Abstract: Our data suggest that TWEAK acts as a pro-inflammatory cytokine in the adipose tissue and that inflammation, but not hypoxia, may be behind its up-regulation in severe obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 30 publications
3
41
1
Order By: Relevance
“…Infl ammation is one of the mechanisms linking obesity, insulin resistance and other metabolic-related disturbances (Wisse, 2004). At the same time, only slight elevation of proinfl ammatory cytokines was observed in the obtained animal model being indicative that current dietary intervention did not induce systemic infl ammation that is observed in severe obesity (Vendrell et al, 2010). The obtained data on altered adipose tissue zinc content in HF-fed animals are in agreement with the previously published articles (Liu et al, 2013;Tallman and Taylor, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Infl ammation is one of the mechanisms linking obesity, insulin resistance and other metabolic-related disturbances (Wisse, 2004). At the same time, only slight elevation of proinfl ammatory cytokines was observed in the obtained animal model being indicative that current dietary intervention did not induce systemic infl ammation that is observed in severe obesity (Vendrell et al, 2010). The obtained data on altered adipose tissue zinc content in HF-fed animals are in agreement with the previously published articles (Liu et al, 2013;Tallman and Taylor, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…This observation emphasizes the differences that exist between cell types in transducing signals from common receptors, thereby mediating distinct biological functions. In line with this finding, it has now been established that the biological activity of TWEAK can be independent of NF-B and requires the activation of alternative cell signaling pathways such as ERK or p38 MAPK signaling (Ando et al, 2006;Sanz et al, 2009;Vendrell et al, 2010). We further demonstrated that ERK and p38 MAPK pathways are indispensable for TWEAK-dependent mitogenic function, a result compatible with the well known central role of these MAPKs in cell proliferation (Zhang and Liu, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…However, the real contribution of each tissue to circulating sTWEAK is unknown. The low level of TWEAK mRNA detected in human adipose tissue (42) suggests that adipose tissue contribution to circulating sTWEAK circulation is minor. Interestingly, our unpublished findings suggest that circulating sTWEAK is negatively correlated with fat mass (under review).…”
Section: Discussionmentioning
confidence: 98%
“…Although TWEAK and its receptor Fn14 are expressed in a variety of organs, including adipose tissue (7), the physiological and patho-physiological roles of this cytokine in an obesity-associated insulin-resistant state remains largely unknown. TWEAK has been described to inhibit adipogenesis (40) and we have recently shown that TWEAK may have a proinflammatory function in human subcutaneous adipocytes (42). However, clinical studies have shown a negative association between † Deceased 7 April 2010.fasting glucose and soluble circulating sTWEAK levels, as well as a decrease of sTWEAK in patients with T2D (24).…”
mentioning
confidence: 99%